Realising Women’s Political Rights in Ukraine - Lesko, Nataliia; Khomyshyn, Iryna; Skochylias-Pavliv , Olha; Lukіanova Halyna; Malets, Marta (Journal of Education Culture and Society, 2023)
Aim. The article attempts to study legal fundamentals of realising women’s political rights in Ukraine. Equal rights for women and men in all spheres of social and political life is the important condition and guarantee for strengthening democracy in Ukraine. Methods. The research was conducted by applying general scientific methods of learning (analysis, synthesis, modelling) and private-scientific methods of learning (historical, retrospective, comparative and legal, formally logical). The general methodological basis of the article is made by dialectics, ensuring comprehensive studying the problems of realising women’s political rights in Ukraine. Results. Having analysed particularities of realising women’s political rights in Ukraine, it is worth noting that since 2010 gender quotas have not been set in the Ukraine’s election legislation until 2015. However, 2015 was the year of the first introduction of gender quotas, but they were not of imperative character. According to the new Election Code of Ukraine of 19 December 2019, gender quotas have become a mandatory regulation at the nomination stage. Conclusions. It is reasonable to make transformation of the stereotypes of the women’s role in politics and to draw more attention to mass media, contributing to extension of women’s political rights and destruction of the bias about women’s position in politics. Gender quotas in the election legislation of Ukraine are of great significance for all members of society in the political sphere, whilst it needs improvement of the administrative and legal mechanisms to ensure gender quotas.